Personalization and Brand Visibility: A Key to Enhancing Customer Satisfaction in E-commerce - Ariani, Ika Adi; Rozi, Fachrur; Muhammad, Amin; Safitri, Eka Dwi (University of Science and Computer Technology, 2025)
E-commerce has transformed consumer behavior by offering convenience, speed, and variety. In this evolving landscape, personalization and brand visibility have become essential strategies for businesses seeking to enhance customer satisfaction. This study investigates how these two factors influence customer satisfaction in the Indonesian e-commerce sector. Adopting a mixed-methods design, the research combines quantitative data from 400 online shoppers with qualitative insights from 20 in-depth interviews. Quantitative data were analyzed using regression analysis and structural equation modeling (SEM), while thematic analysis was employed for qualitative data to extract key patterns and experiences. The findings confirm that personalization—through tailored recommendations, customized interfaces, and targeted communications—positively affects customer satisfaction by increasing perceived relevance and engagement. Similarly, brand visibility—measured by the frequency and consistency of brand exposure across digital platforms—enhances trust and purchase intent. Notably, the study identifies a synergistic effect when personalization and brand visibility are integrated, resulting in up to a 40% increase in satisfaction scores compared to when these strategies are applied individually. Despite these positive outcomes, the study also highlights challenges, including privacy concerns, data management complexity, and market-specific limitations. This research contributes to digital marketing literature by offering a holistic understanding of how personalization and visibility jointly shape customer experiences. The findings provide practical implications for e-commerce businesses aiming to build loyalty and competitive advantage.